INVESTASI MESIN/PERALATAN DALAM PENINGKATAN NILAI PRODUKSI INDUSTRI LOGAM MESIN ELEKTRONIK DAN ANEKA - Ady Soejoto; Dennis Handini (Pendidikan Ekonomi, 2012)
The aim of this research is (1) to know the influence of machine / equipments investment growth on the electronic machine metal industry and various production value in Waru District in year 2002-2007, (2) to describe machine/equipment investment growth, electronic machine metal industry and various production value in Waru District. The study uses descriptive statistics in the form of tables, graph, or diagram through calculation of percentage. To find out the relationship between machine/equipments investment, electronic machine metal industry, and various production value in Waru District, the study uses linear regression with SPSS version 12. In conclusion, there is very unidirectional and strong relation between machine/equipments investment and electronic machine metal industry and various production value. Because F hit value > F tab of hence Ho refused. It means that there is influence between machine/ equipments investment on electronic machine metal industry and variety production value in Waru District.